Trans-anal prolapse of ileo-colic intussusception - Irene Mutua; James Ransom; Dan Kiptoon (Elsevier, 2018)
We present a case report on prolapsed intussusception in an 18-month old patient, managed at Kenyatta National Hospital successfully. Prolapsed intussusception is rare and is mostly misdiagnosed as rectal prolapse. Surgical management is opted due to late presentation at our facility and has good prognosis. Keywords: Trans anal protrusion of intussusception (TAPI), Ileostomy, Rectal prolapse